Automated planning : theory and practice - Ghallab, Malik (Morgan Kaufmann Series in Artificial Intelligence., 2004)
Automated planning technology plays a significant role in a variety of demanding applications, ranging from controlling space vehicles and robots to playing the game of bridge. This book covers both the theory and practice of automated planning. It is useful for researchers, professionals, and graduate students.